Demographic Profiles of Québec's English-speaking Communities Region of Abitibi-Témiscamingue and MRC Abitibi - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

[Dashboards - Quebec and RTS Territories] - Community Health and Social Services Network (CHSSN) (2021)

Children 0 to 5 and their Parents : RTS de l'Abitibi-Témiscamingue - Community Health and Social Services Network (CHSSN) (2016)

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.